Mutational analyses of human eIF5A-1-identification of amino acid residues critical for eIF5A activity and hypusine modification - Cano, Veridiana S. P. [UNESP]; Jeon, Geoung A.; Johansson, Hans E.; Henderson, C. Allen; Park, Jong-Hwan; Valentini, Sandro Roberto [UNESP]; Hershey, John W. B.; Park, Myung Hee (Blackwell Publishing, 2008)
The eukaryotic translation initiation factor 5A (eIF5A) is the only protein that contains hypusine [N-epsilon-(4-amino-2-hydroxybutyl)lysine], which is required for its activity. Hypusine is formed by post-translational modification of one specific lysine (Lys50 for human eIF5A) by deoxyhypusine synthase and deoxyhypusine hydroxylase. To investigate the features of eIF5A required for its activity, we generated 49 mutations in human eIF5A-1, with a single amino acid substitution at the highly conserved residues or with N-terminal or C-terminal truncations, and tested mutant proteins in complementing the growth of a Saccharomyces cerevisiae eIF5A null strain. Growth-supporting activity was abolished in only a few mutant eIF5As (K47D, G49A, K50A, K50D, K50I, K50R, G52A and K55A), with substitutions at or near the hypusine modification site or with truncation of 21 amino acids from either the N-terminus or C-terminus. The inactivity of the Lys50 substitution proteins is obviously due to lack of deoxyhypusine modification. In contrast, K47D and G49A were effective substrates for deoxyhypusine synthase, yet failed to support growth, suggesting critical roles of Lys47 and Gly49 in eIF5A activity, possibly in its interaction with effector(s). By use of a UBHY-R strain harboring genetically engineered unstable eIF5A, we present evidence for the primary function of eIF5A in protein synthesis. When selected eIF5A mutant proteins were tested for their activity in protein synthesis, a close correlation was observed between their ability to enhance protein synthesis and growth, lending further support for a central role of eIF5A in translation.
Keywords: deoxyhypusine synthase; eIF5A; hypusine; post-translational modification; translation initiation